The Myths We Live By - Midgley, Mary (Religion and Beliefs Series, 2003)
Mary Midgley argues in her powerful new book that far from being the opposite of science, myth is a central part of it. In brilliant prose, she claims that myths are neither lies nor mere stories but a network of powerful symbols that suggest particular ways of interpreting the world. Mary Midgley is a moral philosopher and the author of many books including Wickedness , Evolution as a Religion (both Routledge Classics), The Ethical Primate , Science as Salvation , Utopias , Dolphins and Computers , and Science and Poetry . All are published by Routledge. 'For those who haven't yet read Midgley, these essays are an excellent place to start.' - Jon Turney, The Guardian 'An elegant and sane little book. Unusually for a philosopher, Midgley has a superb ear for the use and misuse of language.' - Edward Skidelsky, New Statesman 'She has, perhaps, the sharpest perception of any living thinker of the dangerous extremism that lurks behind so much contemporary scientistic discourse ... Merely as anthologies of contemporary folly, Midgley's books are essential reading ... we have Mary Midgley among us. We should pay attention and be grateful.' - Brian Appleyard, The Sunday Times '[Mary Midgley's] latest book is full of good sense and illumination on many topics ... Midgley's pathbreaking efforts should be warmly welcomed.' - The Philosopher's Magazine 'Mary's voice, sane, clear and brooking no nonsense, speaks crisply from every page, debunking scientific and non-scientific pretensions alike. A chapter each evening will help me keep sane.' - The Sunday Times 'Christian readers will be sympathetic abd find much material for helpful reflection on the topics chosen.' - The Gospel and Our Culture Network